The Genetic risk of asthma: a review of reports on the effect of single nucleotide polymorphisms detected by genome-wide association study on the development and course of asthma using the genes: ORMDL3, ADAM33, DENND1B as examples - Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria (Journal of Education, Health and Sport, 2023)
Asthma, an inflammatory disease of the lower and upper airways, is one of the most common diseases in society. Depending on the source and the population studied, the percentage of asthma patients ranges from 5% to as high as 15%. The development of asthma is believed to be caused by an overlap between the body’s personal propensity to develop the disease and environmental factors. For years, scientists have been studying the genetic basis of asthma. For several years they have had a new weapon in their arsenal - the GWAS method. The use of this method has enabled researchers to discover the relationship between gene variants found in patients and an increased risk of developing asthma.